Penerapan Teori Planned Behavior Dalam Mempengaruhi Niat Remaja Jalanan Menjadi Peer Educator - Meliantha Asmarani Kusumawardani; Syamsulhuda Budi Musthofa; Antono Suryoputro (Dian Nuswantoro Semarang, 2023)
The problem of street children is still a social problem that must be addressed today, including reproductive health issues. However, the efforts that have been made by the government are still not successful, so it needs innovation to provide reproductive health education to street children. One program that is worth trying is peer education. This study aims to determine the factors that influence the intention to become a peer educator of street youth in Semarang City. This study was a quantitative study with a cross-sectional design. The population was 150 street children under the auspices of an NGO partnering with the Department of Social Service. The sampling techniques were purposive sampling and accidental sampling. The sample was 91 respondents. The result showed that 49% of street youth that has the intention to be peer educator was influenced by attitude (p-value = 0,000), subjective norm consisting of parents (p-value = 0,005), friend (p-value = 0,021), NGO companion (p-value = 0,001), perceived control behavior (p-value = 0,000). It is hoped that government, especially the Department of Social Service and NGOs can provide and facilitate a supportive environment for the street youth to have the opportunity to improve their quality of life through peer educators by fulfilling basic needs first before preparing for further matters.